Pulmonary Nocardiosis in an Immunocompetent Patient with Cystic Fibrosis. (15th April 2015) - Schoen, Lucy; Santoro, Jonathan D.; Milla, Carlos; Bhargava, Sumit
Abstract : Nocardia spp. are bacteria of low virulence that cause infection classically in immunocompromised hosts with the lungs as the primary site of infection in the majority of cases. Patients with cystic fibrosis have pulmonary disease characterized by frequent and progressive bacterial infections. Reports of Nocardia spp. isolation in CF are rare in the literature and may represent colonization or active infection, the significance and optimal treatment of which are unknown. We report the second case to date of Nocardia transvalensis pulmonary infection in an immunocompetent patient with CF and the first in a child under the age of eighteen.